2020
DOI: 10.32897/jsikap.v4i2.190
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Mutasi, Motivasi, Dan Kompetensi Terhadap Kinerja Auditor

Abstract: Penelitian ini bertujuan untuk mengetahui apakah mutasi, motivasi, dan kompetensi memberikan pengaruh terhadap kinerja auditor. Penelitian ini menggunakan pendekatan kuantitatif. Penelitian ini menggunakan responden dengan jumlah sebanyak 100 auditor. Hasil kuisioner diolah dengan menggunakan Program SPSS untuk mengetahui pengaruh secara parsial dan simultan variabel mutasi, motivasi, dan kompetensi terhadap kinerja auditor serta mendapatkan persamaan regresi berganda. Hasil analisa berdasarkan hasil olah stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
1
11
0
2
Order By: Relevance
“…The auditor's role is to provide audit report results that are acceptable to management. The results of this study are in line with research (Adisti & Setyohadi, 2019;Kurniawan et al, 2020) which states that a more competent auditor will be more responsive in detecting errors that occur. The increase in work experience and knowledge of the auditor will also improve the auditor's accuracy in conducting audits.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The auditor's role is to provide audit report results that are acceptable to management. The results of this study are in line with research (Adisti & Setyohadi, 2019;Kurniawan et al, 2020) which states that a more competent auditor will be more responsive in detecting errors that occur. The increase in work experience and knowledge of the auditor will also improve the auditor's accuracy in conducting audits.…”
Section: Discussionsupporting
confidence: 89%
“…Personal responsibility regarding the results of the work carried out improves their performance (Asbi Amin, 2019). The study results (Ulfah & Lukiastuti, 2018;Kurniawan et al, 2020;Anggraini & Syofyan, 2020) found that competence had a positive and significant effect on auditor performance. This means that the higher the competence of internal auditors or inspectorate employees, the better the performance of internal auditors/inspectorate employees in carrying out their duties.…”
Section: Introductionmentioning
confidence: 90%
“…Hasil penelitian (Saing, 2018), (Chrishartanto & Said, 2019), (Kurniawan et al, 2020), (Sofiati & Septianto, 2021), (Marlina, 2021), dan (Hartati, 2021) membuktikan bahwa mutasi karyawan dapat mempengaruhi kinerja karyawan, sehingga berdasarkan konsep dan penelitian sebelumnya yang penulis paparkan sehingga dugaan kedua bisa diformulasikan H2: Mutasi mempunyai efek yang positif pada kinerja karyawan Kinerja Kinerja merupakan hasil aktivitas sepanjang kurun waktu periode spesifik serta diukur menurut standar yang pernah ditetapkan lebih dahulu. (Satria, 2021).…”
Section: Mutasiunclassified
“…Hipotesis kedua yaitu mutasi mempunyai dampak yang positif serta signifikan pada kinerja dibuktikan oleh hasil analisis data, hasil ini juga turut membuktikan hasil penelitian dari (Saing, 2018), (Chrishartanto & Said, 2019), (Kurniawan et al, 2020), (Sofiati & Septianto, 2021), (Marlina, 2021), dan (Hartati, 2021). Mutasi merupakan pemindahan karyawan secara vertical dari unit atau departemen tertentu ke unit atau departemen lain bahkan dapat dilakukan di internal organisasi pada wilayah geografis yang berbeda (Ayuningtyas, 2021).…”
Section: Mutasi Terhadap Kinerja Karyawan Universitas Floresunclassified
“…Mutations can be defined as the transfer of functions, responsibilities, and employment status related to employee activities from the old place to the new place so that the employee concerned can obtain maximum job satisfaction and work performance for the organization (Saing, 2018). While Kurniawan et al (2020) state that mutation is a change in the workplace, work function, field of work, responsibilities, and employment status in an organization without any change in salary or level. Synthetically, it can be explained that the mutation is oriented to the employee development function because it aims to increase work efficiency and effectiveness within the organization or company.…”
Section: Employee Mutationmentioning
confidence: 99%